Homoplasy: from detecting pattern to determining process in evolution, but with a secondary role for morphology? - Assis, Leandro C. S.; de Carvalho, Marcelo R.; Wheeler, Quentin D. (Zootaxa, 2011)
David Wake and colleagues provided a thought-provoking review of the concept of homoplasy through the integration, within a phylogenetic framework, of genetic and developmental data (Wake et al. 2011). According to them (p. 1032) “Molecular sequence data have greatly increased our ability to identify homoplastic traits.” This is made clear, for example, in their flow chart for homoplasy detection (Figure 2, p. 1034), wherein homoplasy is discovered through the mapping of “traits of interest” onto a phylogram, a practice common in the molecular phylogenetic paradigm. The “mapping” is usually of morphological characters that are employed to support the chosen (molecular) topology, but which, as a consequence, do not themselves contribute to the formation of those topologies (Assis & Carvalho 2010).